Utilization of Digital Platform-Based Gamification in Akidah Akhlak Learning: A Study of Effectiveness and Student Learning Motivation - diana falhabibah saifur ridzal diana; akbar alifian iswahyuono akbar; adib habibi adib (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
Akidah Akhlak instruction plays a pivotal role in shaping students' faith and moral character; however, its practical implementation often faces challenges due to abstract content delivery and heavy reliance on rote memorization. This study aims to examine the utilization of digital platform-based gamification (such as Quizizz, Kahoot!, Wordwall, Educaplay, and ClassDojo) in enhancing the effectiveness of Akidah Akhlak learning. Utilizing a qualitative approach with a systematic literature review (SLR) method, this research synthesizes findings from prior empirical studies. The results indicate that integrating game mechanics—such as points, leaderboards, badges, and instant feedback—transforms classroom dynamics into a more interactive and engaging environment. Cognitively, quiz-based and interactive multimedia platforms significantly improve students' understanding of complex theological concepts and long-term memory retention. Affectively, positive reinforcement systems like ClassDojo foster character habituation through real-time social recognition. Nevertheless, challenges such as infrastructure limitations, teachers' TPACK readiness, and the risk of over-gamification remain. This study concludes that a balanced integration of digital gamification effectively enhances both cognitive achievement and the internalization of moral values among students.